Clinical Performance of BAL Metagenomic Next-Generation Sequence and Serum (1,3)-β-D-Glucan for Differential Diagnosis of Pneumocystis jirovecii Pneumonia and Pneumocystis jirovecii Colonisation - Liu, Li; Yuan, Mingjuan; Shi, Yi; Su, Xin (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Differentiating Pneumocystis jirovecii infection from colonisation is crucial for appropriate therapy administration. In this study, we evaluated the performance of bronchoalveolar lavage fluid (BAL) metagenomic next-generation sequencing (mNGS) and serum 1,3-β-D-glucan (BDG) tests in differentiating colonisation and infection with P. jirovecii. Methods: From January 2018 to March 2021, 47 patients were enrolled in this study at the Hunan Provincial People’s Hospital. The final diagnosis was used as a reference, and cases were classified into the P. jirovecii pneumonia (PJP) group or P. jirovecii colonisation (PJC) group. Clinical data were recorded. The performances of mNGS and BDG were compared. Result: The fungal load significantly differed between patients with PJP and PJC, with median reads of 3215.79 ± 1797 vs 5.61 ± 0.88 in the PJP and PJC groups, respectively (P < 0.0001). BDG also significantly differed between the two groups, with a median titre of 233.60 ± 39.65 pg/mL in the PJP group and 68.48 ± 19.21 pg/mL in the PJC group (P = 0.0006). The area under the curve was 0.973 (95%CI 0.868–1.007) for mNGS of the BAL and 0.879 (95%CI 0.769–0.989) for the serum BDG. The optimal threshold value for discriminating P. jirovecii infection from colonisation appeared to be 14 reads (sensitivity 83.3%; specificity 95.7%; positive likelihood ratio, 19.2) and BDG = 88.6 pg/mL (sensitivity 79.2%; specificity 92.9%; positive likelihood ratio, 18.2). No correlation between mNGS reads and the BDG titre was found in mNGS-positive patients (r2 = 0.0076, P = 0.583). The levels of lactate dehydrogenase and C-reactive protein were significantly higher in the PJP group than in the PJC group. Conclusion: BAL mNGS and serum BDG are useful adjunct tests that can assist with differentiating between colonisation and infection of P. jirovecii.